Answer: Yes!
Step-by-step explanation:
You correctly answered!
Is this the entire question?
Answer with Step-by-step explanation:
We are given that
![f(x)=\frac{3x-1}{x}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B3x-1%7D%7Bx%7D)
For each real number ![x\neq 0](https://tex.z-dn.net/?f=x%5Cneq%200)
To prove that f is one -to-one.
Proof:Let
and
be any nonzero real numbers such that
![f(x_1)=f(x_2)](https://tex.z-dn.net/?f=f%28x_1%29%3Df%28x_2%29)
By using the definition of f to rewrite the left hand side of this equation
![f(x_1)=\frac{3x_1-1}{x_1}](https://tex.z-dn.net/?f=f%28x_1%29%3D%5Cfrac%7B3x_1-1%7D%7Bx_1%7D)
Then, by using the definition of f to rewrite the right hand side of this equation of ![f(x_1)=f(x_2)](https://tex.z-dn.net/?f=f%28x_1%29%3Df%28x_2%29)
![f(x_2)=\frac{3x_2-1}{x_2}](https://tex.z-dn.net/?f=f%28x_2%29%3D%5Cfrac%7B3x_2-1%7D%7Bx_2%7D)
Equating the expression then we get
![\frac{3x_1-1}{x_1}=\frac{3x_2-1}{x_2}](https://tex.z-dn.net/?f=%5Cfrac%7B3x_1-1%7D%7Bx_1%7D%3D%5Cfrac%7B3x_2-1%7D%7Bx_2%7D)
![3x_1x_2-x_2=3x_2x_1-x_1](https://tex.z-dn.net/?f=3x_1x_2-x_2%3D3x_2x_1-x_1)
![3x_1x_2-3x_1x_2+x_1=x_2](https://tex.z-dn.net/?f=3x_1x_2-3x_1x_2%2Bx_1%3Dx_2)
![x_1=x_2](https://tex.z-dn.net/?f=x_1%3Dx_2)
Therefore, f is one-to-one.
Answer:
pretty sure its D but idk
Step-by-step explanation:
Answer:
91
Step-by-step explanation:
2p+18=200
subtract 18 on both sides
2p=182
Divide 2 on each side
p=91